Construction and validation of the brazilian questionário de respostas socialmente habilidosas segundo relato de professores (QRSH-PR) - Bolsoni-Silva, Alessandra Turini [UNESP]; Marturano, Edna Maria; Loureiro, Sonia Regina (Cambridge University Press (CUP), 2009)
Behavioral problems in preschool children are one of the most frequent motives for seeking psychological care by parents and caregivers. Instruments are considered necessary, created from a Social Skills Training theoretical-practical perspective, which may systematically assist the identification of social skills and behavioral deficits, helping professionals in the prevention and/or reduction of behavioral problems. The purpose of this study was to test the psychometric validity and reliability of an instrument for evaluation of Socially Skilled Responses, from a teacher's perspective (QRSH-PR For this purpose, 260 preschool children were evaluated, differentiated in subgroups without and without behavioral difficulties, based on the Child Behavior Scale (Escala de Comportamento Infantil/ECI-Professor Studies were conducted for construct, discrimination, concurrent and predictive validity. The Cronbach Alpha was calculated to evaluate internal consistency. The obtained results pointed to positive indicators in reference to construct, discrimination, and predictive validity, and even for good internal consistency, indicating that the items consistently measure the construct of social skills, and differentiated children with and without behavioral problems. The questionnaire is considered to be gauged for evaluation of socially skilled responses from preschool children, and applicable in educational and clinical environments. Copyright 2009 by The Spanish Journal of Psychology.
Keywords: QRSH-PR; Questionnaire; Social skills; Validation; anxiety; behavior disorder; Brazil; child; child behavior; comparative study; decision making; factorial analysis; female; human; human relation; male; personality test; prediction and forecasting; preschool child; psychological aspect; psychometry; questionnaire; reproducibility; self concept; social adaptation; teaching; Anxiety; Child; Child Behavior; Child Behavior Disorders; Child, Preschool; Factor Analysis, Statistical; Female; Humans; Interpersonal Relations; Judgment; Male; Personality Assessment; Predictive Value of Tests; Psychometrics; Questionnaires; Reproducibility of Results; Self Concept; Social Adjustment; Teaching